Infecção da corrente sanguínea causada por Pseudomonas aeruginosa resistente aos carbapenêmicos: fatores associados a mortalidade e influência da terapia combinada com polimixina B e imipenem - Teixeira, Jane de Oliveira Gonzaga [UNIFESP] (2011)
Pseudomonas aeruginosa is an important pathogen causing nosocomial bloodstream infections. The treatment of carbapenem-resistant P. aeruginosa is a challenge as the drugs used for this purpose, the polymyxins, have lower activity compared with carbapenems. However, it has been suggested that polymyxins have the ability to make gram-negative bacteria more susceptible to other antibiotics. As carbapenems are considered the main drugs against P. aeruginosa, it would be interesting to demonstrate the efficacy of this combination in vivo, targeting a more effective therapy. Objectives: To evaluate the response of the treatment with polymyxin B versus polymyxin B and carbapenem in patients with nosocomial bloodstream infection caused by carbapenenresistant Pseudomonas aeruginosa and identify factors associated with mortality among those patients Methods: A retrospective cohort study was performed at Hospital São Paulo - UNIFESP, from January 1st, 2000 to December 31, 2009. The identification of patients was done through data collection from the blood cultures report. Patients were initially divided into deaths and survivors, and assessed for exposure to various factors potentially associated with in-hospital mortality and infection-related mortality. Presence of metalobetalactamase was tested trough PCR technique. Results: We studied 69 bloodstream infections caused by carbapenems-resistant P. aeruginosa. Thirthy-five were treated with polymyxin B monotherapy and 34 with combined therapy. In- hospital mortality was 77.1% and 79.4% in the monotherapy group and combined therapy group, respectively (p = 0.819). The infection-related mortality was 42.8% among patients who received monotherapy, and 44.1% in those receiving combined therapy (p = 0.917). Factors associated with mortality were previous use of glycopeptides (OR 10.71, CI95% 1.20 to 95.34, p = 0.033) and Charlson score (OR 1.9, CI95% 1, 22 to 2.94, p = 0.004). Infection-related mortality was associated with the presence of septic shock (OR 9.99, CI95% 1.81 to 55.22, p = 0.006) and parenteral nutrition (OR 7.45, CI95% 1.23 - 45.24, p = 0.029). No statistically significant difference was found between patients with MBLharboring and non-MBL-harboring strains treated with combined therapy. Conclusions: No difference was found between the monotherapy and combined therapy group regarding mortality. Independent factors related to in- hospital mortality were prior use of glycopeptides and the Charlson score. Presence of septic shock and use of parenteral nutrition were independently associated with infection-related mortality.